Prevalence of thyroid dysfunctions in a large, unselected population in Duhok city, Iraqi Kurdistan: A cross-sectional study - Burhan Zaman (PAGEPress Publications, 2021)
Objective: To determine the prevalence of thyroid-stimulating hormone (TSH) alterations and different types of thyroid dysfunctions in both sexes with no age limitations from variety of sources in Duhok province.